PEDAGOGICAL-PSYCHOLOGICAL FACTORS IN THE DEVELOPMENT OF INTELLECTUAL POWER AND ACTIVITY OF YOUTH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The authors noted, pointed to teacher’s assigned tasks, work with talented children creative one of the main areas of activity of the head. Acquire pedagogical and psychological foundations, intellectual potential youth in the educational process, creativity and talent and his appearance, social historical nature, the study of the creative intellectual potential.